The Effectiveness of Lemongrass Oil Against Brown planthopper Nilaparvata lugens Stal. (Hemiptera: Delphacidae) on Rice Plant - Toto Himawan; Rina Rachmawati; Eka Putri Rifandani (University of Brawijaya, 2021)
Rice (Oryza sativa) is the primary food crop in the world. The use of natural pesticides made from essential plants has begun to be developed because it is useful in controlling some plant pests. This study aimed to investigate lemongrass oil's effectiveness in controlling brown planthopper pests in rice plants. This study consist of five concentrations using lemongrass oil and sterile distilled water as control was repeated three times. The highest mortality of brown planthopper was found at 1.6% concentration (100%), while the lowest mortality was 0.1% concentration (26.66%). The lemongrass oil can be used to control brown planthoppers because of the LC50 value at a concentration of 8233.34 ppm (0.8%) and LT50 at 6 HAT.